Glacial lake outburst flood risk assessment using combined approaches of remote sensing, GIS and dam break modelling. Issue 1 (2nd January 2016) - Aggarwal, Arpit; Jain, Sanjay K.; Lohani, Anil K.; Jain, Neha
Abstract : A great number of glacial lakes have appeared in many mountain regions across the world during the last half-century due to receding of glaciers and global warming. In the present study, glacial lake outburst flood (GLOF) risk assessment has been carried out in the Teesta river basin located in the Sikkim state of India. First, the study focuses on accurate mapping of the glaciers and glacial lakes using multispectral satellite images of Landsat and Indian Remote Sensing satellites. For glacier mapping, normalized difference snow index (NDSI) image and slope map of the area have been utilized. NDSI approach can identify glaciers covered with clean snow but debris-covered glaciers cannot be mapped using NDSI method alone. For the present study, slope map has been utilized along with the NDSI approach to delineate glaciers manually. Glacial lakes have been mapped by supervised maximum likelihood classification and normalized difference water index followed by manual editing afterwards using Google Earth images. Second, the first proper inventory of glacial lakes for Teesta basin has been compiled containing information of 143 glacial lakes. Third, analysis of these lakes has been carried out for identification of potentially dangerous lakes. Vulnerable lakes have been identified on the basis of parameters like surface area, position with respect to parent glacier, growth since 2009, slope, distance from the outlet of the basin, presence of supraglacial lakes, presence of other lakes in downstream, condition of moraine, condition of the terrain around them, etc. From these criterions, in total, 18 lakes have been identified as potentially dangerous glacial lakes. Out of these 18 lakes, further analysis has been carried out for the identification of the most vulnerable lake. Lake 140 comes out to be the most vulnerable for a GLOF event. Lastly, for this potentially dangerous lake, different dam break parameters have been generated using satellite data and digital elevation model. The volume and depth have been computed using empirical formulae, and other parameters such as cross-sections from the lake to outlet etc. have been prepared in ArcGIS 9.3. The GLOF which can be triggered by Lake 140 was modelled and simulated using MIKE-11 software's hydrodynamic module. As a result, flood values and hydrograph have been obtained. The flood at lake site comes out to be 2611.136 cumec which get mitigated to 1417.844 cumec at the outlet.